2015
DOI: 10.4238/2015.august.14.23
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of rat osteosarcoma cell apoptosis induced by a combination of low-intensity ultrasound and 5-aminolevulinic acid in vitro

Abstract: ABSTRACT. We investigated the killing effect of low-intensity ultrasound combined with 5-aminolevulinic acid (5-ALA) on the rat osteosarcoma cell line UMR-106. Logarithmic-phase UMR-106 cells were divided into a control group, ultrasound group and 5-ALA group. The cell apoptotic rate, production of reactive oxygen species, and the change in mitochondrial membrane potential were analyzed by flow cytometry; ultrastructural changes were observed by transmission electron microscopy. Using low-intensity ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The US-induced secondary metabolism observed in plant cell cultures could be regulated by low-level ROS, which have been shown to be produced in sonicated cell-free solutions [92,93] and in cells upon exposure to moderate U.S. [94]. This effect has become a background for the sonodynamic therapy of tumours [95,96].…”
Section: Redox Regulation Of Secondary Metabolite Synthesis In Plamentioning
confidence: 99%
“…The US-induced secondary metabolism observed in plant cell cultures could be regulated by low-level ROS, which have been shown to be produced in sonicated cell-free solutions [92,93] and in cells upon exposure to moderate U.S. [94]. This effect has become a background for the sonodynamic therapy of tumours [95,96].…”
Section: Redox Regulation Of Secondary Metabolite Synthesis In Plamentioning
confidence: 99%
“…Left ventricular dysfunction in mice with acute myocardial infarction could be attenuated by LIPUS ( 7 ). Biological effects of reagents and drugs were augmented by LIPUS, such as 5-aminolevulinic acid ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…As observed by some experiments, the tumor inhibitory activity of SDT on tumor cells was mainly to induce cell apoptosis14353940. The pro-apoptotic effect and related bio-mechanisms vary with the type of sonosensitizers used in cancer treatment.…”
Section: Discussionmentioning
confidence: 95%
“…PpIX, a hematorphyrin derivative, was found preferentially accumulated in rapid proliferating cancer cells, and it is sonosensitive18323334. In previous studies, we showed that ALA can be a good sonosensitizer for SDT as it exhibited significant selectivity on tumor tissues and a synergistic inhibition effect with low intensity ultrasound on SAS cells2526273536. In this work, we demonstrated, both in vivo and in vitro , that the combined use of PpIX and LIU can significantly inhibit the proliferation of SAS cells, which acted through the cell cycle arrest and p53-dependent extrinsic apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%